Pengembangan Aplikasi Multimedia Berbasis Web untuk Pembelajaran Alat Musik Tradisional Aceh - Amrullah, M Fahlevi, Zulfikar (LPPM-UNIKI, 2024)
The development of a web-based multimedia application for learning traditional Acehnese musical instruments aims to facilitate the process of learning to recognize and play traditional Acehnese musical instruments. This research employs an educational approach by providing in-depth and engaging content about various traditional Acehnese musical instruments. The application is expected to enhance the interest of both local and international communities in the traditional musical culture of Aceh. The methodology used in the development of this application includes needs analysis, system design, implementation, and evaluation. The needs analysis was conducted by identifying the primary challenge, which is the lack of knowledge about traditional Acehnese musical instruments among elementary to high school students. The system design encompasses a user-friendly interface and the integration of multimedia content to provide an interactive and enjoyable learning experience. The application was implemented using the latest web technologies that support interactive multimedia. Evaluation was carried out through trials with target user groups to gather feedback and improve the application according to user needs. The research results indicate that this application is effective in enhancing students' understanding and interest in traditional Acehnese musical instruments. The application also has the potential to become a significant learning tool for teachers and students in recognizing and preserving the traditional musical culture of Aceh.